La ripetizione e il sublime. Danto, Lyotard, Wathol e la fine (differita) dell’arte - Dario Cecchi (Rivista di Estetica, 2021)
This article compares two philosophers who have a different theoretical origin: respectively, Arthur C. Danto and Jean-François Lyotard. Both of them are interested in the revolutionary character of Andy Warhol’s art. Danto as well as Lyotard argues that Warhol conceives the work of art as a machine: according to the former, it is a philosophical machine; according to the latter, it is a consumerist machine. Nonetheless, the two hypotheses converge on judging Warhol’s art as a turn in the history of art and its relationship to the world. According to Danto, who follows Hegel here, Warhol at the same time interprets and transcends the 1960s and their Zeitgeist. But paradoxically, Warhol’s historical gesture, epitomized by his work Brillo Box, initiates the age of the “end of art”. According to Lyotard, on the contrary, Warhol represents the end of the critical power of modern art, to which the sublime alone can remediate. The two perspectives converge in the idea that the investigation of repetition is the very center of Warhol’s art. Art has now become the pivot of the Western capitalism and consumerist society. Warhol actually explores the different forms and modes of repetition (commodities, icons, symbols) and, in this way, anticipates the confrontation of contemporary art with the “finite infinite” represented by the media world.